PENGARUH PEMBIAYAAN MURABAHAH TERHADAP PERKEMBANGAN USAHA MIKRO KECIL MENENGAH (UMKM) PADA BAITUL MAL WAT- TAMWIL (BMT) - Mulyani Rizki (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2021)
The development of Islamic economics in Indonesia takes place so rapidly. In 1992, BMT was the forerunner of the birth of Islamic banks. Then the development of BMT grew alive after receiving support from the Small Business Business Incubation Foundation (YINBUK) which was initiated by the Indonesian Ulema Council (MUI). Along with this, Islamic financial institutions with a micro scope, refer to Law Number 25 of 1992 concerning Cooperatives and Ministerial Decree No. Baitul Maal wat-Tamwil (BMT) is also increasingly showing its existence. BMT which is legally formal as a sharia microfinance institution with a cooperative legal entity which is different from Islamic banks. The difference is in the legal aspect where Islamic banks are under the auspices of Bank Indonesia (BI) while BMTs are under the State Ministry of Cooperatives and MSMEs.6 Ba'i al-Murabahah, namely buying and selling mabi' with ra's al-mal (cost of goods) plus a number of conditions agreed in the contract.9 In a murabahah contract, the seller must notify the cost of goods he bought and determine a level of profit in addition. Murabaha contracts can be made for purchases by purchase order. In terms of Imam Shafi.I in the book Al-Um, known as Al-Amir bi ash syira.10 According to Ascarya, Murabahah is an Islamic fiqh term which means a certain form of buying and selling when the seller states the cost of acquiring the goods, including the price of the goods and other costs incurred to obtain the goods, and the desired level of profit. Judging from the above phenomenon, Murabahah Financing can affect the development of micro, small and medium enterprises (MSMEs) in BMT. The purpose of this study was to determine how the effect of Murabahah Financing on the development of Micro, Small and Medium Enterprises (MSMEs) in BMT The number of samples in this study was 78 respondents, this study used a quantitative approach. The data collection technique in this study used a questionnaire, and the sampling technique used the incidental sampling method using the slovin formula. The data obtained was then processed using the SPSS 22 application. The results of this study indicate that the value of t count > t table (4.207 > 1.993) and a significant value of 0.000 < 0.05 which means that partially the Murabahah variable has a positive and significant effect on the development of MSMEs in BMT.